Minimum Competency Assessment to Measure Mathematical Literacy of Junior High School Students - Syaifuddin, Mohammad (LPPM Undiksha, 2022)
Referring to the results of international tests, both PISA and TIMSS, Indonesia continues to strive to improve students' mathematical literacy skills through various policies. However, most students performed better in terms of literacy than on the arithmetic test. This study aims to develop a valid and reliable minimum competency assessment instrument to measure and describe the mathematical literacy competence of junior high school students in carrying out the minimum competency assessment (MCA). This type of Research & Development (R&D) research uses the development stages of the modified Oriondo and Antonio models. This study involved 60 students. The subjects used for the trial were 15 junior high school students. The methods used to collect data are observation and questionnaires. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative and quantitative analysis. The results showed that 17 questions were valid and reliable, with Alpha reliability of 0.853, and suitable for measuring the numeracy literacy competence of junior high school students. The average numeracy literacy competence of junior high school students is 53.3, categorized as 'less.' The research findings suggest that teachers can utilize the MCA test to assess students' mathematical literacy and identify areas where students need to improve classroom learning.